Legal Readiness on Timor-Leste to face Transnational Crime in the ASEAN Economic Community (AEC) - Marsal, Antonino Pedro (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2023)
ABSTRACTThe existence of the ASEAN community and the global community, which has played an active role in the development of unstoppable, has brought various influences, both positive and negative. The people of Timor-Leste will certainly not be spared and will experience the impact of globalization. Therefore there are 2 important points that must be prepared by the government and parliament. First, the government must take anticipatory steps against transnational crimes in the era of the ASEAN Economic Community (AEC). Second, the Government and parliament must prepare adequate legal products to anticipate transnational crimes that will arise, and also carry out international cooperation to harmonization the law with ASEAN member States. In this study using a normative type of research reciting laws regarding transnational crimes. With the problems that have been explained from the beginning, it is concluded as follows: The responsibility of the government to increase the capacity of law enforcement officials, especially the police, to conduct continuous training to become professionals to combat and anticipate transnational crimes that will arise. Provide supporting facilities for police officers in carrying out their duties. conduct international cooperation among ASEAN member states to strengthen the rules of international law to combat transnational crime. ASEAN AEC Keywords Transnational Crime Timor-Leste